Modeling music popularity as an epidemic: insights from the Brazilian market - Oliveira, Gabriel P.; Vassio, Luca; Silva, Ana Paula Couto da; Moro, Mirella M. (Anais do Brazilian Workshop on Social Network Analysis and Mining (BraSNAM), 2025)
Social networks have drastically changed the music market scenario, enabling songs to reach massive audiences in record time. Given the fast-paced nature of music popularity, this work investigates whether epidemic models can effectively capture how songs gain traction. We apply the Susceptible-Infected-Recovered (SIR) model to analyze music virality and success in Brazil. Virality reflects a song’s rapid surge in popularity, whereas success represents its long-term endurance. By comparing the model’s fit for both trajectories, we assess its strengths and limitations in capturing music popularity trends. Our findings reveal that SIR provides a better fit for virality than for long-term success, reinforcing the differences between both processes and, consequently, offering a new perspective on how songs become popular in the digital age.